UHPC admixture prepared based on seawater, high-durability UHPC prepared based on sea sand and preparation method of UHPC admixture

Through the waterproof UHPC admixture prepared based on seawater, the problems of shortage of freshwater resources and seawater desalination environmental pollution in sea sand UHPC production are solved, and the high waterproof performance of sea sand UHPC and the efficient utilization of seawater resources are achieved.

CN119874246APending Publication Date: 2025-04-25SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411883878.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When producing sea sand UHPC in a near marine environment, it faces problems such as shortage of freshwater resources, humid climate and harsh construction environment. At the same time, seawater desalination has high costs and environmental pollution risks.

Method used

Waterproof UHPC admixtures prepared based on seawater, including polycarboxylic acid powder, defoaming agent, concentrated pretreated seawater, aluminum chloride, solid calcium chloride and crystalline calcium chloride, are used to pretreat seawater and compound components to generate admixtures with waterproof properties, and are adjusted through double doping to meet the working performance requirements.

Benefits of technology

It improves the waterproofing ability of sea sand UHPC, and is suitable for UHPC with high waterproofing requirements, realizes efficient utilization of seawater resources, reduces environmental pollution, and has no subsequent environmental protection problems.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a UHPC admixture prepared on the basis of seawater, high-durability UHPC prepared on the basis of sea sand and a preparation method thereof.The admixture comprises polycarboxylic acid powder, a defoaming agent, concentrated pretreated seawater, aluminum chloride, solid calcium chloride and crystalline calcium chloride, by adding the admixture into the sea sand UHPC, the waterproof capacity of the sea sand UHPC can be enhanced, and the service life of the UHPC is prolonged. The method is suitable for preparing UHPC with high waterproof requirements. In the preparation process, the seawater is pretreated, and the concentrated and pretreated seawater is further processed and each component is added during compounding, so that a material B with a waterproof characteristic is generated; the material A is added on the basis of the material B, that is, the UHPC special material is adjusted in real time in use in a two-mixing mode so as to meet the working performance requirement. By adopting the preparation method disclosed by the invention, the effects of improving the traditional technology and simultaneously realizing the resource utilization of the seawater sand can be achieved, and meanwhile, the effect of no subsequent environmental protection problem is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building materials, and more specifically, to a UHPC admixture prepared based on seawater, a high-durability UHPC prepared based on sea sand, and a preparation method thereof. Background Art

[0002] In recent years, UHPC and its components have been vigorously developed due to their excellent mechanical properties, durability, applicability and economy. They are one of the important fixed materials for construction in high-performance component systems. UHPC, the full name of which is Ultra-High Performance Concrete, is a high-performance material composed of high-performance cementitious materials, early strength aggregates, functional admixtures and additives. It can be widely used in various structural parts and construction scenarios. As the technology of preparing UHPC with sea sand as raw material becomes more and more mature, the preparation of sea sand UHPC usually takes materials nearby, and sea sand is used as raw material for the production of building components. For the production of sea sand UHPC near the marine environment, there are difficulties such as shortage of fresh water resources, humid climate and harsh construction environment. The current annual water consumption for construction is extremely high. Groundwater and river water are the main sources of natural water for construction, but the supply of groundwater and river water is limited by resources and environmental conditions, and is far from meeting the national demand for construction water. Desalination of seawater has become an important part of construction water. However, desalination of seawater is not only costly, but also causes environmental problems. The elimination of some marine organisms such as small fish and plankton will disrupt the food chain in the ocean. In addition, how to deal with the high-purity salt produced by desalination is also an important issue. If these high-salt wastewaters are discharged into the sea, local aquatic crops will be seriously damaged. If the seawater is used directly without desalination, it will cause rust on steel fibers and other metal objects, which will easily cause quality problems and reduced durability, and increase subsequent maintenance costs. In addition, due to the complex production and use environment of sea sand UHPC, various admixtures are often required, especially in humid and rainy conditions, and waterproofing agents need to be added to improve the working performance of sea sand UHPC. Waterproofing agent is an admixture that can penetrate into concrete. It can fill the micropores and cracks in concrete to form a complete waterproof layer, effectively preventing moisture from penetrating into the concrete. In addition, waterproofing agents can also react with hydrates in concrete to form a dense cement-based substance, thereby improving the water resistance and durability of concrete.

[0003] After analyzing the composition of seawater, it can be found that the main components of seawater include cations Na+, K+, Ca2+, Mg2+ and Sr2+, anions C1-, S042-, Br-, HCO3-, CO32- and F-, and H3BO3 in molecular form, which together account for 99.9% of the salt content of seawater. How to efficiently utilize the effective components in seawater, reduce the damage to the environment during the use of seawater, and prepare high-performance sea sand UHPC in a humid and rainy environment has become an important technical problem that technicians in this field need to solve. Summary of the invention

[0004] The invention discloses a waterproof UHPC admixture prepared based on seawater. The admixture comprises the following components: polycarboxylic acid powder, a defoamer, concentrated pretreated seawater, aluminum chloride, solid calcium chloride and crystalline calcium chloride.

[0005] Preferably, the components of the admixture are calculated by weight as follows: 2 to 13 parts by weight of polycarboxylic acid powder, 0.05 to 0.22 parts by weight of defoaming agent, 78 to 89 parts by weight of concentrated pretreated seawater, 1 to 4 parts by weight of aluminum chloride, 6 to 13 parts by weight of solid calcium chloride, and 8 to 12 parts by weight of crystalline calcium chloride.

[0006] Preferably, the concentrated pretreated seawater is pretreated by boiling.

[0007] A method for preparing a waterproof UHPC admixture based on seawater comprises the following steps:

[0008] Step S1: taking seawater, boiling it at high temperature for 5 to 20 minutes, filtering it to remove impurities, gases and volatile substances, and obtaining concentrated pretreated seawater;

[0009] Step S2: taking polycarboxylic acid powder and defoaming agent and mixing them to obtain material A;

[0010] Step S3: injecting concentrated pretreated seawater into the reactor to heat it up, and then maintaining a constant temperature after heating;

[0011] Step S4: Weigh solid calcium chloride and dissolve it in 80° C. hot water in a reaction kettle, mix and stir evenly, and keep stirring at a fixed speed;

[0012] Step S5: After the solid calcium chloride is fully dissolved, continue stirring until the next step begins;

[0013] Step S6: After cooling to 48-52° C., weighing crystalline calcium chloride and dissolving it in a reaction kettle, maintaining a fixed rotation speed, and continuously stirring after the crystalline calcium chloride is fully dissolved, and then keeping the temperature to react after the stirring is completed to prepare a composite liquid;

[0014] Step S7: After the temperature of the composite liquid in the reaction kettle is lowered, the catalyst, aluminum chloride and hydrochloric acid are added, stirred evenly, and then the stirring is continued for 15 to 30 minutes, and then the stirring speed is increased, 30% sodium hydroxide solution is added, and the pH value is adjusted to 5 to 6 to obtain a mixed solution;

[0015] Step S8: filtering the mixed solution obtained in the previous step through a 100-mesh sieve to obtain material B;

[0016] Step S9: In the preparation process of sea sand UHPC, material B is added first, and then material A is added on the basis of material B.

[0017] Preferably, in step S3, the concentrated pretreated seawater is heated to 80°C within 1 hour and maintained at a constant temperature.

[0018] Preferably, in step S4, the fixed speed of stirring after the solid calcium chloride is added is determined according to the diameter of the reactor;

[0019] When the diameter of the reactor is less than 0.8 meters, the fixed speed is 300r / min;

[0020] When the diameter of the reactor is 0.8 to 1.5 meters, the fixed speed is 400 to 450 r / min;

[0021] When the diameter of the reactor is 1.5-2 meters, the fixed rotation speed is 600-650 r / min.

[0022] Preferably, in step S5, specifically: after the solid calcium chloride is fully dissolved, stirring is continued at a speed of 270 to 330 r / min for 10 to 20 min until the next step begins.

[0023] Preferably, in step S6, the fixed rotation speed maintained when the crystalline calcium chloride is dissolved in the reactor is determined according to the diameter of the reactor;

[0024] When the diameter of the reactor is less than 0.8 meters, the fixed speed is 300r / min;

[0025] When the diameter of the reactor is 0.8 to 1.5 meters, the fixed speed is 400 to 450 r / min;

[0026] When the diameter of the reactor is 1.5 to 2 meters, the fixed speed is 600 to 650 r / min;

[0027] After the crystallized calcium chloride is fully formed, the stirring time is continued for 10 to 20 minutes, and the heat preservation reaction time after the stirring is completed is 24 to 48 hours.

[0028] Preferably, in step S7, specifically: wait for the composite liquid in the reaction kettle to cool to 20-30° C., add the catalyst, aluminum chloride and hydrochloric acid at a speed of 180-220 r / min, stir evenly, and continue stirring for 15-30 minutes, increase the speed to 360-440 r / min, and then add 30% sodium hydroxide solution after speeding up.

[0029] Preferably, in step S7, specifically: a fixed amount of hydrochloric acid solution is added to the composite liquid each time, and after each addition, it needs to be stirred at a speed of 360-440r / min for at least 5 minutes, and then a drop of suspension is dipped with a glass rod and dropped on a pH test paper, and then the acidity and alkalinity of the test solution are detected by comparing the color change of the test paper with the standard colorimetric card. If the set pH value is not reached, a fixed amount of hydrochloric acid solution is added to repeat the above operation until the pH value of the test result reaches 5-6, and then stirring is continued for 30-60 minutes. After the pH value is detected to be 5-6, a fixed amount of 30% sodium hydroxide solution is added to the prepared B material composite liquid each time, and after each addition, it needs to be stirred at a speed of 360-440r / min for at least 5 minutes.

[0030] The present invention also provides a high-durability UHPC prepared based on sea sand, comprising: UHPC made of sea sand and the above-mentioned UHPC admixture.

[0031] The present invention provides a waterproof UHPC admixture based on seawater, wherein the admixture includes polycarboxylic acid powder, defoaming agent, concentrated pretreated seawater, aluminum chloride, solid calcium chloride and crystalline calcium chloride. By adding the admixture to sea sand UHPC, the waterproof ability of sea sand UHPC can be enhanced, and the admixture is suitable for preparing UHPC with high waterproof requirements. In terms of the preparation process, the present invention adopts the method of pretreating seawater, further processing and adding various components to the concentrated pretreated seawater during compounding to generate material B with waterproof properties; material A is added to material B, that is, through the two-mixing method, the UHPC special material is adjusted in real time during use to meet the working performance requirements. By adopting the preparation method of the present invention, it is possible to achieve the effect of improving traditional technology and realizing the resource utilization of seawater sand at the same time, and at the same time achieve the effect of no subsequent environmental protection problems. DETAILED DESCRIPTION

[0032] The present invention discloses a waterproof UHPC admixture based on seawater and a preparation method thereof, wherein the seawater is pretreated, and the concentrated pretreated seawater is further processed and various components are added during compounding to generate a B material with waterproof properties; the A material is added to the B material, that is, through a two-mixing method, the UHPC special material is adjusted in real time during use to meet the working performance requirements. By adopting the preparation method of the present invention, the effects of improving traditional technology and realizing the resource utilization of seawater sand can be achieved at the same time.

[0033] The technical solutions in the embodiments of the present invention are described clearly and in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The invention provides a waterproof UHPC admixture prepared based on seawater. The admixture comprises the following components: polycarboxylic acid powder, a defoamer, concentrated pretreated seawater, aluminum chloride, solid calcium chloride and crystalline calcium chloride.

[0035] The cost of desalination treatment is high and the purification effect is difficult to achieve the best. If the seawater is directly applied to UHPC without treatment, there will be problems such as high risk of cracking and metal corrosion caused by high cement, water reducing agent and water consumption. In an embodiment of the present invention, the concentrated pre-treated seawater is to treat ordinary seawater in a simple and easy-to-implement manner such as heating and boiling to remove unstable organic matter, gas components and volatile substances, and the concentration of seawater is controlled. The main components of seawater are cations Na+, K+, Ca2+, Mg2+ and Sr2+, anions Cl-, S042-, Br-, HCO3-, CO32-, F-, etc., and H3BO3 in molecular form, which together account for 99.9% of the salinity of seawater. In order to reduce the risks of direct use of seawater, this embodiment combines the treated concentrated pretreated seawater with polycarboxylic acid powder, defoaming agent, aluminum chloride, solid calcium chloride and crystalline calcium chloride. These components are compounded with concentrated pretreated seawater to generate an admixture with waterproof properties, so that the main components in the seawater are effectively utilized, greatly reducing the waste discharged into the natural environment.

[0036] Preferably, the components of the admixture are calculated by weight as follows: 2 to 13 parts by weight of polycarboxylic acid powder, 0.05 to 0.22 parts by weight of defoamer, 78 to 89 parts by weight of concentrated pretreated seawater, 1 to 4 parts by weight of aluminum chloride, 6 to 13 parts by weight of solid calcium chloride, and 8 to 12 parts by weight of crystalline calcium chloride. The polycarboxylic acid powder, defoamer, aluminum chloride, solid calcium chloride and crystalline calcium chloride in the weight proportions provided in this embodiment are prepared with concentrated pretreated seawater to form a mixture with improved UHPC functionality. The mixture is added to the premix of sea sand UHPC, which can react with the cementitious material in the sea sand UHPC to generate compounds such as hydrated calcium chlorosilicate and calcium chloroaluminate, which fill the gaps in the mortar, improve the waterproofness, and make the concrete dense, early strong, pressure-resistant, impermeable, and frost-resistant and waterproof. The admixture of this embodiment has the appearance of a light yellow oily liquid, and is suitable for preparing UHPC with high waterproofing requirements. It can also be used for painting waterproof layers, plugging leaks, mixing cement mortar plaster layers, etc.

[0037] Preferably, the concentrated pretreated seawater is boiled to remove unstable organic matter, gas components and volatile substances from the seawater, and the concentration of the seawater is further increased after boiling.

[0038] A method for preparing a waterproof UHPC admixture based on seawater comprises the following steps:

[0039] Step S1: taking seawater, boiling it at high temperature for 5 to 20 minutes, filtering it to remove impurities, gases and volatile substances, and obtaining concentrated pretreated seawater;

[0040] Step S2: taking polycarboxylic acid powder and defoaming agent and mixing them to obtain material A;

[0041] Step S3: injecting concentrated pretreated seawater into the reactor to heat it up, and then maintaining a constant temperature after heating;

[0042] Step S4: Weigh solid calcium chloride and dissolve it in 80° C. hot water in a reaction kettle, mix and stir evenly, and keep stirring at a fixed speed;

[0043] Step S5: After the solid calcium chloride is fully dissolved, continue stirring until the next step begins;

[0044] Step S6: After cooling to 48-52° C., weighing crystalline calcium chloride and dissolving it in a reaction kettle, maintaining a fixed rotation speed, and continuously stirring after the crystalline calcium chloride is fully dissolved, and then keeping the temperature to react after the stirring is completed to prepare a composite liquid;

[0045] Step S7: After the temperature of the composite liquid in the reaction kettle is lowered, the catalyst, aluminum chloride and hydrochloric acid are added, stirred evenly, and then the stirring is continued for 15 to 30 minutes, and then the stirring speed is increased, 30% sodium hydroxide solution is added, and the pH value is adjusted to 5 to 6 to obtain a mixed solution;

[0046] Step S8: filtering the mixed solution obtained in the previous step through a 100-mesh sieve to obtain material B;

[0047] Step S9: In the preparation process of sea sand UHPC, material B is added first, and then material A is added on the basis of material B.

[0048] This preparation process treats seawater from two directions:

[0049] First, pre-treat the seawater; after boiling, remove unstable organic matter, gas components and volatile substances. The main components in seawater mainly refer to the components with a concentration greater than 1mg / lkg in seawater. There are five cations Na+, K+, Ca2+, Mg2+ and Sr2+, six anions C1-, S042-, Br-, HCO3-, CO32-, F-, and H3BO3 in molecular form, which together account for 99.9% of the salt content of seawater. So it is called the main component. Other substances are added to the main components to compound them into various functional admixtures (early strength type, slow setting type, accelerating setting type, rapid setting type, flocculation type, waterproof type, expansion type, antifreeze type, thickening type, etc.).

[0050] Secondly, the seawater admixture and special material are adaptively treated; aluminum chloride, solid calcium chloride and crystalline calcium chloride are added to the concentrated and treated seawater after pretreatment, and added in steps to generate material B with waterproof properties, so that it has the function of improving the waterproof effect of sea sand UHPC. Then, different proportions of material A are added to the material B, that is, through the two-mixing method, the UHPC special material is adjusted in real time during use to meet the working performance requirements. The two materials are combined to first prepare material B that meets the durability and mechanical properties, and the working performance is controlled by adjusting the proportion of material A to prepare UHPC with various characteristics of excellent performance. It is often only necessary to adjust the components with the greatest influence in material B to configure different types of UHPC or UHPC premix admixtures.

[0051] When adjusting adaptability in the traditional mode, no distinction is made between A and B materials. Each adjustment is made by adjusting different proportions of all components to test different types of UHPC or UHPC premix admixtures. The components with large and small impacts in the admixtures are not distinguished. A joint adjustment method is adopted, resulting in long R&D time, time-consuming test batching, many quality control links, low production efficiency and high costs.

[0052] The preparation method has the following advantages:

[0053] High utilization rate of seawater; compared with the general seawater desalination process, the marine life will be destroyed after the seawater enters the desalination plant, causing the food chain in the ocean to be disordered, and the high-purity salt produced by seawater desalination will cause serious damage to local aquatic crops. This preparation method can realize the resource utilization of seawater while using seawater to make antifreeze sea sand UHPC admixture to achieve the effect of no subsequent environmental protection problems.

[0054] Improvement of the performance of sea sand UHPC; the admixture prepared by the preparation method is added to the sea sand UHPC premix, and the amount of material B is 3% to 7% of the mass of the cementitious material in the sea sand UHPC. It can react with the cementitious material to generate water-containing calcium chlorosilicate, calcium chloroaluminate and other compounds, fill the gaps in the mortar, improve the waterproofness, and make the concrete dense, early strong, pressure-resistant, impermeable, and frost-resistant. The chloride metal salt waterproofing agent has the appearance of a light yellow oily liquid, with the properties of rapid setting, early strength, pressure resistance, waterproofing, impermeability, and frost resistance. It is suitable for the preparation of UHPC with high waterproofing requirements, and can also be used for brushing waterproof layers, plugging leaks, mixing cement mortar plaster layers, etc.

[0055] Preferably, in step S3, the concentrated pretreated seawater is heated to 80°C within 1 hour and maintained at a constant temperature.

[0056] Preferably, in step S4, the fixed speed of stirring after the solid calcium chloride is added is determined according to the diameter of the reactor;

[0057] When the diameter of the reactor is less than 0.8 meters, the fixed speed is 300r / min;

[0058] When the diameter of the reactor is 0.8 to 1.5 meters, the fixed speed is 400 to 450 r / min;

[0059] When the diameter of the reactor is 1.5-2 meters, the fixed rotation speed is 600-650 r / min.

[0060] Preferably, in step S5, specifically: after the solid calcium chloride is fully dissolved, stirring is continued at a speed of 270 to 330 r / min for 10 to 20 min until the next step begins.

[0061] Preferably, in step S6, the fixed rotation speed maintained when the crystalline calcium chloride is dissolved in the reactor is determined according to the diameter of the reactor;

[0062] When the diameter of the reactor is less than 0.8 meters, the fixed speed is 300r / min;

[0063] When the diameter of the reactor is 0.8 to 1.5 meters, the fixed speed is 400 to 450 r / min;

[0064] When the diameter of the reactor is 1.5 to 2 meters, the fixed speed is 600 to 650 r / min;

[0065] After the crystallized calcium chloride is fully formed, the stirring time is continued for 10 to 20 minutes, and the heat preservation reaction time after the stirring is completed is 24 to 48 hours.

[0066] Preferably, in step S7, specifically: wait for the composite liquid in the reaction kettle to cool to 20-30° C., add the catalyst, aluminum chloride and hydrochloric acid at a speed of 180-220 r / min, stir evenly, and continue stirring for 15-30 minutes, increase the speed to 360-440 r / min, and then add 30% sodium hydroxide solution after speeding up.

[0067] Preferably, in step S7, specifically: a fixed amount of hydrochloric acid solution is added to the composite liquid each time, and after each addition, it needs to be stirred at a speed of 360-440r / min for at least 5 minutes, and then a drop of suspension is dipped with a glass rod and dropped on a pH test paper, and then the acidity and alkalinity of the test solution are detected by comparing the color change of the test paper with the standard colorimetric card. If the set pH value is not reached, a fixed amount of hydrochloric acid solution is added to repeat the above operation until the pH value of the test result reaches 5-6, and then stirring is continued for 30-60 minutes. After the pH value is detected to be 5-6, a fixed amount of 30% sodium hydroxide solution is added to the prepared B material composite liquid each time, and after each addition, it needs to be stirred at a speed of 360-440r / min for at least 5 minutes.

[0068] The following is described through multiple embodiments:

[0069] Embodiment 1:

[0070] Step S1: taking seawater, boiling it at high temperature for 5 to 20 minutes, filtering it to remove impurities, gases and volatile substances, and obtaining concentrated pretreated seawater;

[0071] Step S2: 2 to 13 parts by weight of polycarboxylic acid powder and 0.05 to 0.22 parts by weight of a defoaming agent are mixed and stirred to obtain material A;

[0072] Step S3: injecting 78 to 89 parts by weight of concentrated pretreated seawater into a reactor and heating the reactor to 80° C. within 1 hour, and maintaining a constant temperature after heating;

[0073] Step S4: Weigh 6 to 13 parts by weight of solid calcium chloride, dissolve it in 80° C. hot water in a reaction kettle, mix and stir evenly, and keep stirring at a fixed speed;

[0074] Step S5: After the solid calcium chloride is fully dissolved, stirring is continued at a speed of 270 to 330 r / min for 10 to 20 min until the next step begins;

[0075] Step S6: After cooling to 48-52° C., weigh 8-12 parts by weight of crystalline calcium chloride and dissolve it in a reaction kettle, maintain a fixed speed, and continue stirring for 10-20 minutes after the crystalline calcium chloride is fully dissolved. After the stirring is completed, keep the temperature for reaction for 24-48 hours to prepare a composite liquid;

[0076] Step S7: After the temperature of the composite liquid in the reaction kettle is reduced to 20-30° C., a catalyst, 1-4 parts by weight of aluminum chloride and hydrochloric acid are added at a speed of 180-220 r / min, and stirred evenly, and then stirring is continued for 15-30 minutes, and the speed is increased to 360-440 r / min. After the speed is increased, a 30% sodium hydroxide solution is added, and the pH value is adjusted to 5-6 to obtain a mixed solution;

[0077] Step S8: filtering the mixed solution obtained in the previous step through a 100-mesh sieve to obtain material B;

[0078] Step S9: In the preparation process of sea sand UHPC, material B is added first, and then material A is added on the basis of material B.

[0079] Embodiment 2:

[0080] Step S1: taking seawater, boiling it at high temperature for 5 minutes, filtering it to remove impurities, gases and volatile substances, and obtaining concentrated pretreated seawater;

[0081] Step S2: 2 parts by weight of polycarboxylic acid powder and 0.05 parts by weight of defoaming agent are mixed and stirred to obtain material A;

[0082] Step S3: inject 78 parts by weight of concentrated pretreated seawater into the reactor and heat it to 80° C. within 1 hour, and then keep the temperature constant;

[0083] Step S4: Weigh 6 parts by weight of solid calcium chloride, dissolve it in 80° C. hot water in a reaction kettle, mix and stir evenly, and keep stirring at a fixed speed;

[0084] Step S5: After the solid calcium chloride is fully dissolved, stirring is continued at a speed of 270 r / min for 10 min until the next step begins;

[0085] Step S6: After cooling to 48° C., weigh 8 parts by weight of crystalline calcium chloride and dissolve it in a reaction kettle, maintain a fixed speed, and continue stirring for 10 minutes after the crystalline calcium chloride is fully dissolved. After the stirring is completed, keep the temperature for reaction for 24 hours to prepare a composite liquid;

[0086] Step S7: After the temperature of the composite liquid in the reaction kettle is reduced to 20° C., the catalyst, 1 part by weight of aluminum chloride and hydrochloric acid are added at a speed of 180 r / min, stirred evenly, and then stirred for 15 minutes, and the speed is increased to 360 r / min. After the speed is increased, 30% sodium hydroxide solution is added, and the pH value is adjusted to 5 to obtain a mixed solution;

[0087] Step S8: filtering the mixed solution obtained in the previous step through a 100-mesh sieve to obtain material B;

[0088] Step S9: In the preparation process of sea sand UHPC, material B is added first, and then material A is added on the basis of material B.

[0089] Embodiment 3:

[0090] Step S1: taking seawater, boiling it at high temperature for 12.5 minutes, filtering it to remove impurities, gases and volatile substances, and obtaining concentrated pretreated seawater;

[0091] Step S2: 12.5 parts by weight of polycarboxylic acid powder and 0.135 parts by weight of defoaming agent are mixed and stirred to obtain material A;

[0092] Step S3: injecting 83.5 parts by weight of concentrated pretreated seawater into the reactor and heating the reactor to 80° C. within 1 hour, and maintaining a constant temperature after heating;

[0093] Step S4: Weigh 9.5 parts by weight of solid calcium chloride, dissolve it in 80° C. hot water in a reaction kettle, mix and stir evenly, and keep stirring at a fixed speed;

[0094] Step S5: After the solid calcium chloride is fully dissolved, stirring is continued at a speed of 300 r / min for 15 min until the next step begins;

[0095] Step S6: After cooling to 50° C., weigh 10 parts by weight of crystalline calcium chloride and dissolve it in a reaction kettle, maintain a fixed speed, and continue stirring for 15 minutes after the crystalline calcium chloride is fully dissolved. After the stirring is completed, keep the temperature for reaction for 36 hours to prepare a composite liquid;

[0096] Step S7: After the temperature of the composite liquid in the reaction kettle is reduced to 25° C., the catalyst, 2.5 parts by weight of aluminum chloride and hydrochloric acid are added at a speed of 200 r / min, and the mixture is stirred evenly and then stirred for 22.5 min. The speed is increased to 400 r / min, and after the speed is increased, a 30% sodium hydroxide solution is added, and the pH value is adjusted to 5.5 to obtain a mixed solution;

[0097] Step S8: filtering the mixed solution obtained in the previous step through a 100-mesh sieve to obtain material B;

[0098] Step S9: In the preparation process of sea sand UHPC, material B is added first, and then material A is added on the basis of material B.

[0099] Embodiment 4:

[0100] Step S1: taking seawater, boiling it at high temperature for 20 minutes, filtering it to remove impurities, gases and volatile substances, and obtaining concentrated pretreated seawater;

[0101] Step S2: 13 parts by weight of polycarboxylic acid powder and 0.22 parts by weight of defoaming agent are mixed and stirred to obtain material A;

[0102] Step S3: inject 89 parts by weight of concentrated pretreated seawater into the reactor and heat it to 80° C. within 1 hour, and then maintain a constant temperature;

[0103] Step S4: Weigh 13 parts by weight of solid calcium chloride, dissolve it in 80° C. hot water in a reaction kettle, mix and stir evenly, and keep stirring at a fixed speed;

[0104] Step S5: After the solid calcium chloride is fully dissolved, stirring is continued at a speed of 330 r / min for 20 min until the next step begins;

[0105] Step S6: After cooling to 52° C., weigh 12 parts by weight of crystalline calcium chloride and dissolve it in a reaction kettle, maintain a fixed speed, and continue stirring for 20 minutes after the crystalline calcium chloride is fully dissolved. After the stirring is completed, keep the temperature for reaction for 48 hours to prepare a composite liquid;

[0106] Step S7: After the temperature of the composite liquid in the reaction kettle is reduced to 30° C., the catalyst, 4 parts by weight of aluminum chloride and hydrochloric acid are added at a speed of 220 r / min, stirred evenly, and then stirred for 30 minutes, and the speed is increased to 440 r / min. After the speed is increased, 30% sodium hydroxide solution is added, and the pH value is adjusted to 6 to obtain a mixed solution;

[0107] Step S8: filtering the mixed solution obtained in the previous step through a 100-mesh sieve to obtain material B;

[0108] Step S9: In the preparation process of sea sand UHPC, material B is added first, and then material A is added on the basis of material B.

[0109] The present invention provides a waterproof UHPC admixture based on seawater, wherein the admixture includes polycarboxylic acid powder, defoaming agent, concentrated pretreated seawater, aluminum chloride, solid calcium chloride and crystalline calcium chloride. By adding the admixture to sea sand UHPC, the waterproof ability of sea sand UHPC can be enhanced, and the admixture is suitable for preparing UHPC with high waterproof requirements. In terms of the preparation process, the present invention adopts the method of pretreating seawater, further processing and adding various components to the concentrated pretreated seawater during compounding to generate material B with waterproof properties; material A is added to material B, that is, through the two-mixing method, the UHPC special material is adjusted in real time during use to meet the working performance requirements. By adopting the preparation method of the present invention, it is possible to achieve the effect of improving traditional technology and realizing the resource utilization of seawater sand at the same time, and at the same time achieve the effect of no subsequent environmental protection problems.

[0110] The above is a detailed introduction to the preparation of waterproof UHPC admixture based on seawater and the preparation method thereof provided by the present invention. For those skilled in the art, according to the ideas of the embodiments of the present invention, there may be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as limiting the present invention.

Claims

1. A UHPC admixture prepared based on seawater, characterized in that: The additive comprises the following components: polycarboxylic acid powder, defoamer, concentrated pretreated seawater, aluminum chloride, solid calcium chloride and crystalline calcium chloride.

2. The UHPC admixture prepared based on seawater according to claim 1, characterized in that: The components of the admixture are calculated by weight as follows: 2 to 13 parts by weight of polycarboxylic acid powder, 0.05 to 0.22 parts by weight of defoaming agent, 78 to 89 parts by weight of concentrated pretreated seawater, 1 to 4 parts by weight of aluminum chloride, 6 to 13 parts by weight of solid calcium chloride, and 8 to 12 parts by weight of crystalline calcium chloride.

3. The method for preparing a UHPC admixture based on seawater according to any one of claims 1 to 2, characterized in that: The following steps are included: Step S1: taking seawater, boiling it at high temperature for 5 to 20 minutes, filtering it to remove impurities, gases and volatile substances, and obtaining concentrated pretreated seawater; Step S2: taking polycarboxylic acid powder and defoaming agent and mixing them to obtain material A; Step S3: injecting concentrated pretreated seawater into the reactor to heat it up, and then maintaining a constant temperature after heating; Step S4: Weigh solid calcium chloride and dissolve it in 80° C. hot water in a reaction kettle, mix and stir evenly, and keep stirring at a fixed speed; Step S5: After the solid calcium chloride is fully dissolved, continue stirring until the next step begins; Step S6: After cooling to 48-52° C., weighing crystalline calcium chloride and dissolving it in a reaction kettle, maintaining a fixed rotation speed, and continuously stirring after the crystalline calcium chloride is fully dissolved, and then keeping the temperature to react after the stirring is completed to prepare a composite liquid; Step S7: After the temperature of the composite liquid in the reaction kettle is lowered, the catalyst, aluminum chloride and hydrochloric acid are added, stirred evenly, and then the stirring is continued for 15 to 30 minutes, and then the stirring speed is increased, 30% sodium hydroxide solution is added, and the pH value is adjusted to 5 to 6 to obtain a mixed solution; Step S8: filtering the mixed solution obtained in the previous step through a 100-mesh sieve to obtain material B; Step S9: In the preparation process of sea sand UHPC, material B is added first, and then material A is added on the basis of material B.

4. The method for preparing a UHPC admixture based on seawater according to claim 3, characterized in that: In step S3, the concentrated pretreated seawater is heated to 80°C within 1 hour and maintained at a constant temperature.

5. The method for preparing a UHPC admixture based on seawater according to claim 3, characterized in that: In step S4, the fixed speed of stirring after the solid calcium chloride is added is determined according to the diameter of the reactor; When the diameter of the reactor is less than 0.8 meters, the fixed speed is 300r / min; When the diameter of the reactor is 0.8 to 1.5 meters, the fixed speed is 400 to 450 r / min; When the diameter of the reactor is 1.5-2 meters, the fixed rotation speed is 600-650 r / min.

6. The method for preparing a UHPC admixture based on seawater according to claim 3, characterized in that: In step S5, specifically, after the solid calcium chloride is fully dissolved, stirring is continued at a speed of 270 to 330 r / min for 10 to 20 minutes until the next step begins.

7. The method for preparing a UHPC admixture based on seawater according to claim 3, characterized in that: In step S6, the fixed rotation speed maintained when the crystalline calcium chloride is dissolved in the reactor is determined according to the diameter of the reactor; When the diameter of the reactor is less than 0.8 meters, the fixed speed is 300r / min; When the diameter of the reactor is 0.8 to 1.5 meters, the fixed speed is 400 to 450 r / min; When the diameter of the reactor is 1.5 to 2 meters, the fixed speed is 600 to 650 r / min; After the crystallized calcium chloride is fully formed, the stirring time is continued for 10 to 20 minutes, and the heat preservation reaction time after the stirring is completed is 24 to 48 hours.

8. The method for preparing a UHPC admixture based on seawater according to claim 3, characterized in that: In step S7, specifically: wait for the composite liquid in the reaction kettle to cool to 20-30°C, add the catalyst, aluminum chloride and hydrochloric acid at a speed of 180-220 r / min, stir evenly, and continue stirring for 15-30 minutes, increase the speed to 360-440 r / min, and then add 30% sodium hydroxide solution after speeding up.

9. The method for preparing a UHPC admixture based on seawater according to claim 8, characterized in that: In step S7, specifically: a fixed amount of hydrochloric acid solution is added to the composite liquid each time, and after each addition, it needs to be stirred at a speed of 360-440 r / min for at least 5 minutes, and the pH value of the acidity and alkalinity is tested. If the set pH value is not reached, a fixed amount of hydrochloric acid solution is added again and the above operation is repeated until the pH value of the test result reaches 5-6. At this time, stirring is continued for 30-60 minutes. After the pH value is detected to be 5-6, a fixed amount of 30% sodium hydroxide solution is added to the prepared B material composite liquid each time, and after each addition, it needs to be stirred at a speed of 360-440 r / min for at least 5 minutes.

10. A high-durability UHPC prepared based on sea sand, characterized in that: include: UHPC made of sea sand, and the UHPC admixture according to any one of claims 1 to 9.